PARTISIPASI POLITIK MASYARAKAT KOTA PEKANABARU PADA PEMILIHAN UMUM KEPALA DAERAH TAHUN 2013 (Studi Evaluasi RW 11 Kelurahan Tuah Karya Kecamatan Tam - Gemelly Octavia S; Acmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Post dated September 4, 2013 Riau did the democratic party is the regional head election of Governor and Deputy Governor of Riau for five subsequent periods. On Selection is done directly in Riau Province abstentions bloom coloring organizing various City and County in Riau, one of which is the city of Pekanbaru that once the capital of Riau province. The research looked high and low levels of political participation of people in Pekanbaru in Riau regional election in 2013 (Evaluation Study RW 11 Sub Tuah work Handsome District of Pekanbaru). In this study devoted to measure political participation in the conventional form. In addition, the study also aims to determine the factors that affect people's political participation and the level of satisfaction of the people in the process of implementation of the General Election in 2013 by using the theory according to participation. This study is a descriptive quantitative research, then to analyze the data presented in the form of numbers. This study questionnaire and wawancarayang mneggunakan aims to obtain information in ini.jenis research data used are primary data and secondary data.Keywords: Level of Participation, Election, and the voters list